Telecoupling 2019
DOI: 10.1007/978-3-030-11105-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Export-Oriented Crop Production

Abstract: and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commercial gain • You may freely distribute the URL identifying the publication in the public portal ? Take down policyIf you believe that this document breaches c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Given that PV is still an eclectic but rapidly evolving field, we present here a joint and encompassing analysis to better understand the use and effects of PV processes in a range of local contexts. We focus on the Global South because it is where colonial legacies (Jayaprakash and Hickey, 2019), weak institutional structures and continuous power struggles (Di Gregorio et al, 2019), as well as increasing pressures on natural assets (Levers et al, 2019) drive some of the most drastic impacts and rapid landscape transformations. It is also where the increasing global demand for natural assets are largely borne, especially by local stakeholders (Chaplin-Kramer et al, 2019;IPBES, 2019).…”
Section: Case Studiesmentioning
confidence: 99%
“…Given that PV is still an eclectic but rapidly evolving field, we present here a joint and encompassing analysis to better understand the use and effects of PV processes in a range of local contexts. We focus on the Global South because it is where colonial legacies (Jayaprakash and Hickey, 2019), weak institutional structures and continuous power struggles (Di Gregorio et al, 2019), as well as increasing pressures on natural assets (Levers et al, 2019) drive some of the most drastic impacts and rapid landscape transformations. It is also where the increasing global demand for natural assets are largely borne, especially by local stakeholders (Chaplin-Kramer et al, 2019;IPBES, 2019).…”
Section: Case Studiesmentioning
confidence: 99%
“…One example of this, is the glo-balization of agricultural production, where international trade chains accelerate habitat degradation in places far from the site of consumption (Friis et al 2015). It is widely studied that the large spatial footprint of export-oriented agriculture is responsible for large environmental costs, including local negative effects such as soil degradation, regional impacts due to excessive freshwater use or nutrient and pesticide runoff, and global concerns such as carbon emissions and biodiversity loss due to land conversion for agriculture (Levers and Müller 2019). Lenzen et al (2012), for example, showed that a significant number of species are threatened because of international trade along complex routes where consumers in developed countries (which we prefer to refer as North-Global here) cause threats to species through their demand for commodities that are produced in South-Global countries (such as coffee, tea, sugar, textiles, fish, and other manufactured goods).…”
Section: Globality: the Local-global Relationshipmentioning
confidence: 99%